Strategic Leadership In Indonesia's Commitment To Building A Blue Economy-Based Marine Economy - Arga Yudhistira; Widodo Widodo; Panji Suwarno; Tomi Aris (LPPM Universitas Trunojoyo Madura, 2022)
Leadership can be seen as an instrument in an effort to influence and control a person or group of people to cooperate in achieving certain goals. The Blue Economy is expected to be able to answer the dependence between the economy and the ecosystem as well as the negative impacts of economic activities including climate change and global warming. The principles contained in the blue economy can be a golden key in national development planning. The purpose of this study is to find out how important strategic leadership is in Indonesia's commitment to building a blue economy-based marine economy. The approach used in this research is qualitative - descriptive with the researcher as the main research instrument and the design approach used is descriptive-explanative. the findings in this study found that the role of leadership is very crucial in realizing the success of development with a blue economy approach, Indonesia's abundant natural resources will be meaningless if there is no role of leaders who are able to manage and mobilize all their potential. It is important that all parties involved are involved in helping to create a prosperous marine economy based on a blue economy. The demand for marine and fishery resource-based development to be used as a driving force in national economic development.